2020
DOI: 10.1128/jvi.00034-20
|View full text |Cite
|
Sign up to set email alerts
|

Specialization for Cell-Free or Cell-to-Cell Spread of BAC-Cloned Human Cytomegalovirus Strains Is Determined by Factors beyond the UL128-131 and RL13 Loci

Abstract: It is widely held that clinical isolates of human cytomegalovirus (HCMV) are highly cell associated, and mutations affecting the UL128-131 and RL13 loci that arise in culture lead to the appearance of a cell-free spread phenotype. The bacterial artificial chromosome (BAC) clone Merlin (ME) expresses abundant UL128-131, is RL13 impaired, and produces low infectivity virions in fibroblasts, whereas TB40/e (TB) and TR are low in UL128-131, are RL13 intact, and produce virions of much higher infectivity. Despite t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 79 publications
1
19
1
Order By: Relevance
“…Our data demonstrate that mAbs against the essential viral glycoproteins B and H have the capacity to slow cell-associated HCMV spread. Interestingly and contrary to previous observations [38,75,76], we found that this inhibitory effect was independent of the target cell-type and the mAb concentrations as the respective anti-gB and anti-gH mAbs prevented HCMV spread equally efficiently in HFF and APRE-19 cells (Figure 4e,f). However, within the human host it seems possible that other cell types exist which may exhibit increased or reduced sensitivity to the mAbs that were tested in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our data demonstrate that mAbs against the essential viral glycoproteins B and H have the capacity to slow cell-associated HCMV spread. Interestingly and contrary to previous observations [38,75,76], we found that this inhibitory effect was independent of the target cell-type and the mAb concentrations as the respective anti-gB and anti-gH mAbs prevented HCMV spread equally efficiently in HFF and APRE-19 cells (Figure 4e,f). However, within the human host it seems possible that other cell types exist which may exhibit increased or reduced sensitivity to the mAbs that were tested in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Fluorescence-based assays for quantitative measurement of HCMV spread have been described previously [46,49,76]. However, these assays have not been utilized to: (i) compare the viral spread in different target cell types of HCMV, (ii) have been performed with an only limited number of antigen target specificities or, (iii) not in a live cell imaging setting to allow for monitoring of plaque expansion in a timely manner.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast-adapted HCMV strains that spread efficiently via the cell-free route also form small foci of infected cells in the presence of neutralizing antibodies, and this antibody-resistance is sometimes used to define cell-associated transmission of these strains [ 33 , 36 , 54 , 55 ]. This appears appropriate as other approaches to capture cell-free HCMV, e.g., by agarose or methyl cellulose overlays result in a similar focus size, cannot be further reduced by neutralizing antibodies [ 19 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trimer alone is sufficient for entry into fibroblasts ( Kabanova et al, 2016 ) whereas Pentamer, always required for infection in all other cell types ( Zhou et al, 2015 ; Kabanova et al, 2016 ), extends viral tropism through recognition of specific receptors recently identified ( Martinez-Martin et al, 2018 ; Xiaofei et al, 2019 ). Although cell type restricted receptors explain the tropism specificity, the molecular mechanism responsible for viral infectivity depends on several factors including glycoprotein isoforms, relative ratio of the complexes, RL13 locus and still non identified loci ( Stanton et al, 2010 ; Zhou et al, 2013 , 2015 ; Zhang et al, 2018 ; Schultz et al, 2020 ). In our system, we speculate that a 10-times reduction of infectivity, due to the absence of UL116, may be a consequence of the reduced levels of gH-based complexes on viral particles that cannot support priming of the whole population of gB impairing efficient membrane fusion in about 1/10 of the events.…”
Section: Discussionmentioning
confidence: 99%